As duas noções de phantasia e o surgimento das paixões em Aristóteles - Judenice Alves da Costa (2024)
The thesis seeks a solution to the problem that made the interpreters of Aristotelian passions spend a lot of effort to solve it. This difficulty concerns the question of whether the noun phantasia found in the definitions of some passions corresponds to that notion of the same name investigated in the third book of De anima. Moss and Scheiter answer the question affirmatively but differ as to the conception to be adopted. The former says that passions are aroused only by quasi-perceptual appearances (phantasiai) that happen to be accompanied by opinion (doxa). Scheiter, in turn, considers that those cannot be the only causes of passions since their content corresponds to something previously perceived. According to this author, the content of the images (phantasiai) involved in the emergence of passions is highly complex, and therefore cannot be grasped by the sensitive perception in action. Faced with this limitation, Scheiter distinguishes passions into classes, namely, those that are provoked by the sequence of pleasurable and painful images and those motivated by opinion. In opposition to the two authors, Nussbaum and Fortenbaugh state that the noun phantasia present in the definition of some passions does not correspond to the notion examined in the text that deals with the soul, and therefore, it is plausible to say that it derives from the verb phainetai, which has the meanings of opinion and belief. From this derivation, the authors infer that opinion is the only cognition involved in passions. Faced with these divergent positions, we propose a theoretical model that reconciles both positions. This means that, according to us, most passions originate from the memory of something that is accompanied by expectation as a future-oriented opinion. Furthermore, due to their complexity, we note the participation of empirical judgment in the manifestation of some of them.